2013
DOI: 10.1177/1474651413500698
|View full text |Cite
|
Sign up to set email alerts
|

The tolerability and safety of DPP-4 inhibitors for the treatment of older people with type 2 diabetes mellitus: an observational study

Abstract: Aims/introduction: Despite type 2 diabetes mellitus being up to five times more prevalent in patients aged ≥65 years compared with patients <65 years of age, this population is surprisingly less well studied. Dipeptidyl peptidase (DPP)-4 inhibitor treatment is an option for this older patient group, but clinical practice data for this drug class are sparse in this population. The study examined the efficacy and tolerability of DPP-4 inhibitors in older patients with type 2 diabetes whilst focusing on particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“… P: 100 P ≥ 65 years: 98 P using DPP-4 inhibitors: 26 P using other antidiabetic agents: 72 Not reported Acute ischemic stroke severity measured with the modified Rankin Scale score at discharge and with in-hospital mortality. Viljoen et al 2013 [ 46 ] (Search 3B) Observational study To study the efficacy and tolerability of DPP-4 inhibitors in older patients with type 2 diabetes whilst focusing on particular pertinent aspects relevant to care of older persons. P: 431 P ≥ 65 years: 431 P using DPP-4 inhibitors: 129 P never treated with DPP-4 inhibitors: 302 Not reported Hypoglycaemia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… P: 100 P ≥ 65 years: 98 P using DPP-4 inhibitors: 26 P using other antidiabetic agents: 72 Not reported Acute ischemic stroke severity measured with the modified Rankin Scale score at discharge and with in-hospital mortality. Viljoen et al 2013 [ 46 ] (Search 3B) Observational study To study the efficacy and tolerability of DPP-4 inhibitors in older patients with type 2 diabetes whilst focusing on particular pertinent aspects relevant to care of older persons. P: 431 P ≥ 65 years: 431 P using DPP-4 inhibitors: 129 P never treated with DPP-4 inhibitors: 302 Not reported Hypoglycaemia.…”
Section: Resultsmentioning
confidence: 99%
“…Nine observational studies compared patients treated with DPP-4 inhibitors with patients not receiving DPP-4 inhibitors [ 46 ]; other antidiabetic drugs [ 33 , 35 , 45 , 49 , 51 ]; or between cases and controls [ 36 , 47 , 48 ]. These studies reported on the following outcomes: hypoglycaemia, fractures, disability after stroke (with the modified Rankin scale), cardiovascular events, hospitalisation for heart failure, hospitalisation for sepsis, and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we also found that DPP-4 inhibitors were prescribed as the second most common drugs for the oldest old patients. A recent retrospective study on DDP-4 inhibitors prescribed to elderly diabetes patients (median age 70 years, range 60–92 years) found that median A1C improved from 8.3 to 7.4 % and DDP-4 inhibitors treated patients had a lower rate of documented hypoglycemia than the non-DPP-4 inhibitors treated group (3 vs. 8 %) [ 22 ]. Therefore, DPP-4 inhibitors would be an attractive choice for oldest old patients for its lower rate of hypoglycemia and neutral weight effects.…”
Section: Discussionmentioning
confidence: 99%